Acute Coronary Syndrome: An Unusual Consequence of GERD - Chui Man Carmen Hui; Santosh K. Padala; Michael Lavelle; Mikhail T. Torosoff; Xinjun Cindy Zhu; Mandeep S. Sidhu (Case Reports in Cardiology)
We report a case of an 83-year-old man with history of coronary artery disease and gastroesophageal reflux disease (GERD) who presented with sudden onset nocturnal dyspnea. He was diagnosed with non-ST elevation myocardial infarction based on the electrocardiographic changes and cardiac biomarker elevation. Cardiac catheterization revealed chronic three-vessel coronary artery disease, with 2 patent grafts and 2 chronically occluded grafts. While at the hospital, the patient experienced a similar episode of nocturnal dyspnea, prompting a barium esophagram, which was suggestive of a stricture in the distal esophagus from long-standing GERD. We hypothesized that he had myocardial ischemia due to increased oxygen demand from uncontrolled GERD symptoms. He had no further ischemic episodes after increasing the dose of antireflux medication over a 6-month follow-up. After presenting our case, we review the literature on this atypical presentation of GERD causing acute coronary syndrome and discuss potential mechanisms.